Identification of Functional HLA-A*01:01–Restricted Epstein-Barr Latent Membrane Protein 2–Specific T-Cell Receptors . (18th August 2020) - Huisman, Wesley; Gille, Ilse; van der Maarel, Lieve E; Hageman, Lois; Morton, Laura T; de Jong, Rob C M; Heemskerk, Mirjam H M; Amsen, Derk; Falkenburg, J H Frederik; Jedema, Inge
Abstract: Background: Adoptive transfer of genetically engineered T cells expressing antigen-specific T-cell receptors (TCRs) is an appealing therapeutic approach for Epstein-Barr virus (EBV)–associated malignancies of latency type II/III that express EBV antigens (LMP1/2). Patients who are HLA-A*01:01 positive could benefit from such products, since no T cells recognizing any EBV-derived peptide in this common HLA allele have been found thus far. Methods: HLA-A*01:01–restricted EBV-LMP2–specific T cells were isolated using peptide major histocompatibility complex (pMHC) tetramers. Functionality was assessed by production of interferon gamma (IFN-γ) and cytotoxicity when stimulated with EBV-LMP2–expressing cell lines. Functionality of primary T cells transduced with HLA-A*01:01–restricted EBV-LMP2–specific TCRs was optimized by knocking out the endogenous TCRs of primary T cells (∆TCR) using CRISPR-Cas9 technology. Results: EBV-LMP2–specific T cells were successfully isolated and their TCRs were characterized. TCR gene transfer in primary T cells resulted in specific pMHC tetramer binding and reactivity against EBV-LMP2–expressing cell lines. The mean fluorescence intensity of pMHC-tetramer binding was increased 1.5–2 fold when the endogenous TCRs of CD8 + T cells was knocked out. CD8 +/∆TCR T cells modified to express EBV-LMP2–specific TCRs showed IFN-γ secretion and cytotoxicity toward EBV-LMP2–expressing malignant cell lines. Conclusions: We isolated the first functional HLA-A*01:01–restricted EBV-LMP2–specific T-cell populations and TCRs, which can potentially be used in future TCR gene therapy to treat EBV-associated latency type II/III malignancies. Abstract : Here we identify the first HLA-A*01:01–restricted Epstein-Barr virus Latent Membrane Protein 2 (EBV-LMP2)–specific T-cell population and show that these T-cell populations and T cells modified to express the LMP2-specific T-cell receptor showed IFN-γ secretion and cytotoxicity toward EBV-LMP2–expressing malignant cell lines.